Laparoscopic-Assisted Transgastric ERCP: A Single-Institution Experience. (21st March 2018) - Habenicht Yancey, Katherine; McCormack, Lauren Katherine; McNatt, Stephen Samuel; Powell, Myron Sheavictor; Fernandez, Adolfo Zachariah; Westcott, Carl Joseph
Abstract : Background . Laparoscopic-assisted transgastric endoscopic retrograde cholangiopancreatography (LAERCP) is used for treatment in patients after Roux-en-Y gastric bypass (RYGB), where transoral access to the biliary tree is not possible. We describe our technique and experience with this procedure. Methods . Electronic medical record search was performed from September 2012 to January 2016, identifying patients who underwent LAERCP per operative records. Charts were reviewed for demographic, clinical, and outcomes data. Results . Sixteen patients were identified. Average time since bypass was 6.9 years, and length of stay was 3.7 days. Five patients underwent simultaneous cholecystectomy. Eleven patients, or 43%, had cholecystectomy more than 2 years previously. ERCP with sphincterotomy was completed in 15 of 16 patients (94%). Our technique involves access to the bypassed stomach via a laparoscopically placed 15 mm port. We observed one major complication of post-ERCP necrotizing pancreatitis. No minor complications nor mortalities were seen in our series. Conclusion . Biliary obstruction can occur many years after RYGB and cholecystectomy. Our findings suggest that RYGB patients may be at a higher risk of primary CBD stone formation. LAERCP is a reliable option for common bile duct (CBD) clearance; our technique of LAERCP is technically simple and associated with low complication rate, making it appealing to surgeons not trained in advanced laparoscopy.